A phase 1a/1b trial of CSF-1R inhibitor LY3022855 in combination with durvalumab or tremelimumab in patients with advanced solid tumors - Falchook, Gerald S; Peeters, Marc; Rottey, Sylvie; Dirix, Luc Y; Obermannova, Radka; Cohen, Jonathan E; Perets, Ruth; Frommer, Ronnie Shapira; Bauer, Todd M; Wang, Judy S; Carvajal, Richard D; Sabari, Joshua; et al. (Investigational new drugs, 2021)
Background LY3022855 is a recombinant, immunoglobulin, human monoclonal antibody targeting the colony-stimulating factor-1 receptor. This phase 1 trial determined the safety, pharmacokinetics, and antitumor activity of LY3022855 in combination with durvalumab or tremelimumab in patients with advanced solid cancers who had received standard anti-cancer treatments. Methods In Part A (dose-escalation), patients received intravenous (IV) LY3022855 25/50/75/100 mg once weekly (QW) combined with durvalumab 750 mg once every two weeks (Q2W) IV or LY3022855 50 or 100 mg QW IV with tremelimumab 75/225/750 mg once every four weeks. In Part B (dose-expansion), patients with non-small cell lung cancer (NSCLC) or ovarian cancer (OC) received recommended phase 2 dose (RP2D) of LY3022855 from Part A and durvalumab 750 mg Q2W. Results Seventy-two patients were enrolled (median age 61 years): Part A = 33, Part B = 39. In Part A, maximum tolerated dose was not reached, and LY3022855 100 mg QW and durvalumab 750 mg Q2W was the RP2D. Four dose-limiting equivalent toxicities occurred in two patients from OC cohort. In Part A, maximum concentration, area under the concentration-time curve, and serum concentration showed dose-dependent increase over two cycles of therapy. Overall rates of complete response, partial response, and disease control were 1.4%, 2.8%, and 33.3%. Treatment-emergent anti-drug antibodies were observed in 21.2% of patients. Conclusions LY3022855 combined with durvalumab or tremelimumab in patients with advanced NSCLC or OC had limited clinical activity, was well tolerated. The RP2D was LY3022855 100 mg QW with durvalumab 750 mg Q2W. ClinicalTrials.gov ID: NCT02718911 (Registration Date: May 3, 2011).
Keywords: senioři; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; senioři nad 80 let; monoklonální protilátky; maximální tolerovaná dávka; Middle Aged; plocha pod křivkou; mužské pohlaví; nádory plic; Antibodies, Monoclonal; nádory vaječníků; Adult; Antineoplastic Agents; Aged, 80 and over; nemalobuněčný karcinom plic; ženské pohlaví; protinádorové látky; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; receptory faktoru stimulujícího kolonie; Carcinoma, Non-Small-Cell Lung; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; Area Under Curve; protokoly protinádorové kombinované chemoterapie; Maximum Tolerated Dose; dospělí; Receptors, Colony-Stimulating Factor; Female; Aged; Ovarian Neoplasms; Lung Neoplasms; lidé; Male